The determinants of immigrants' skill composition - Esra Karapınar Kocağ; Yutong Li; Cristina Raluca Popescu (Journal of Risk and Financial Management, 2022)
Movements of labor across the world is an ongoing debate in the literature in terms of its drivers and results in sending and receiving areas. Skill composition of immigrant labor has been discussed by several papers, although they generally focused on visa policies or firm level productivity. However, this paper focuses on the relationship between immigrants' educational attainment and government budgeting on research and development (R&D). Panel data analysis is applied for European countries, along with instrumental variable approach as a robustness check. Findings reveal that higher budget allocation for R&D is associated with higher skill level of immigrants within overall immigrant population. This finding is driven by young immigrants whose ages are between 25 and 34 and female immigrants in these countries, suggesting that this relationship varies among sub-groups of immigrants, which would have significant policy implications. Hence, the novel and original approach of the paper resides in the deciding factors of immigrants' skill composition.
Keywords: 650; sustainable development; economic growth; competitiveness; education; high-skilled labor immigrants; human resources; innovation; labor demand mechanism; labor market; panel data; R&D expenditure; Sustainable Development Goals (SDGs); well-being